Use of MitraClip for mitral valve repair in patients with acute mitral regurgitation following acute myocardial infarction: Effect of cardiogenic shock on outcomes (IREMMI Registry). Issue 6 (18th February 2021) - Estévez‐Loureiro, Rodrigo; Shuvy, Mony; Taramasso, Maurizio; Benito‐Gonzalez, Tomas; Denti, Paolo; Arzamendi, Dabit; Adamo, Marianna; Freixa, Xavier; Villablanca, Pedro; Krivoshei, Lian; Fam, Neil; Spargias, Konstantinos; et al.
Abstract: Objectives: To assess outcomes in patients with acute mitral regurgitation (MR) following acute myocardial infarction (AMI) who received percutaneous mitral valve repair (PMVR) with the MitraClip device and to compare outcomes of patients who developed cardiogenic shock (CS) to those who did not (non‐CS). Background: Acute MR after AMI may lead to CS and is associated with high mortality. Methods: This registry analyzed patients with MR after AMI who were treated with MitraClip at 18 centers within eight countries between January 2016 and February 2020. Patients were stratified into CS and non‐CS groups. Primary outcomes were mortality and rehospitalization due to heart failure. Secondary outcomes were acute procedural success, functional improvement, and MR reduction. Multivariable Cox regression analysis evaluated association of CS with clinical outcomes. Results: Among 93 patients analyzed (age 70.3 ± 10.2 years), 50 patients (53.8%) experienced CS before PMVR. Mortality at 30 days (10% CS vs. 2.3% non‐CS; p = .212) did not differ between groups. After median follow‐up of 7 months (IQR 2.5–17 months), the combined event mortality/re‐hospitalization was similar (28% CS vs. 25.6% non‐CS; p = .793). Likewise, immediate procedural success (90% CS vs. 93% non‐CS; p = .793) and need for reintervention (CS 6% vs. non‐CS 2.3%, p = .621) or re‐admission due to HF (CS 13% vs. NCS 23%, p = .253) at 3 months did not differ. CS was not independently associated with the combined end‐point (hazard ratio 1.1; 95% CI, 0.3–4.6; p = .889). Conclusions: Patients found to have significant MR during their index hospitalization for AMI had similar clinical outcomes with PMVR whether they presented in or out of cardiogenic shock, provided initial hemodynamic stabilization was first achieved before PMVR.